Francisco de Toledo, admirador y émulo de la «tiranía» inca - Ravi Mumford, Jeremy (2011)
Viceroy Francisco de Toledo (1569-81) both reviled and admired the Incas. Surprisingly, he identified exactly the same aspects of their rule to praise and to condemn. To supply a legal justification for the Spanish conquest of Tawantinsuyu, Toledo and his advisers set out to prove that the Incas met the definition of tyranny in Castilian law, as explained by Aristotle and codified in the Siete Partidas. Tyranny was defined by specific elements: state surveillance and control, a climate of fear, the destruction of civil society, social leveling, and a monopoly by the state over its subjects’ time, labor, and property. But even while condemning the Inca regime for these methods, Toledo came to believe that these methods had enabled the Incas to rule well and to create a prosperous society in the Andes. The viceroy self-consciously emulated the same aspects of Inca rule that he invoked to prove that they were tyrants.